1997
DOI: 10.1007/pl00005059
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to d-amphetamine after its repeated administration: evidence in EEG and behaviour

Abstract: After repeated administration of cocaine or d-amphetamine, a sensitization to their behavioural effects is frequently observed instead of a tolerance. In a previous study, it was shown that a moderate dose of d-amphetamine produced a pattern of EEG power spectrum which indicated a selective activation of D1-like dopamine receptors, whereas a larger dose induced a selective increase of power in the alpha-1 frequency band and, to a lesser degree, in the alpha-2 band, suggesting an additional activation of D2-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
(18 reference statements)
7
8
0
Order By: Relevance
“…These results are similar to changes induced by 0.6 mg/kg amphetamine (Stahl et al, 1997) and 20 mg/kg cocaine (Ferger et al, 1996). Lower doses of amphetamine or cocaine do not cause changes in either acute or chronic treatment (Ferger et al, 1996;Stahl et al, 1997), indicating that neural adaptation requires strong stimulation of dopamine receptors.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…These results are similar to changes induced by 0.6 mg/kg amphetamine (Stahl et al, 1997) and 20 mg/kg cocaine (Ferger et al, 1996). Lower doses of amphetamine or cocaine do not cause changes in either acute or chronic treatment (Ferger et al, 1996;Stahl et al, 1997), indicating that neural adaptation requires strong stimulation of dopamine receptors.…”
Section: Discussionsupporting
confidence: 73%
“…Haloperidol could also block acute apomorphine activity but not after chronic exposure, indicating a diminishing D2 receptor component. However, activation of D2 receptors after acute and/or repeated administration of (large doses of) psychostimulants leads to the activation of alpha1 band (7.0∼ 9.5 Hz) and alpha2 band (9.75∼12.5 Hz) that overlap with Alpha (8∼13 Hz) in this study (Kropf et al, 1989;Kropf and Kuschinsky, 1993;Ferger et al, 1994;Ferger and Kuschinsky, 1995;Ferger et al, 1996;Stahl et al, 1997). Delta1 and Delta2 band powers showed consistent increases unrelated to apomorphine treatment.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Studies by Lukas et al (1988Lukas et al ( , 1990Lukas et al ( , 1995 have consistently reported an increase in alpha activity after cocaine, as well as other drugs of abuse, concurrent with episodic periods of euphoria. Similar to the clinical data, some animal studies have reported that acute cocaine and amphetamine treatment results in enhanced alpha activity, which was strongest in the alpha-1 bandwidth (7-9.5 Hz) and was blocked by D1 dopamine antagonists (Stahl et al, 1997;Ferger et al, 1994).…”
Section: Discussionsupporting
confidence: 69%